Ubiquitous and significant anaerobic oxidation of methane in freshwater lake sediments - Martinez-Cruz, Karla; Sepulveda-Jauregui, Armando; Casper, Peter; Anthony, Katey Walter; Smemo, Kurt A.; Thalasso, Frederic (My University, 2018)
Anaerobic oxidation of methane (AOM) is a microbial process that consumes dissolved methane (CH4) in anoxic sediments and soils and mitigates CH4 release to the atmosphere. The degree to which AOM limits global biospheric CH4 emissions is not fully understood. In marine sediments, where the process was first described, AOM is responsible for oxidizing >90% of the CH4 produced. More recently, AOM has been observed in soils, peatlands, and freshwater ecosystems. In lakes, where sediment anoxia, organic carbon turnover, and CH4 production are common, AOM is not well studied but could represent a significant CH4 sink and constraint on emissions. Here, we present evidence for the occurrence of AOM in the sediment of thirteen lakes that span a global climatic and trophic gradient. We further quantified and modeled AOM patterns and studied potential microbial controls of AOM using laboratory incubations of sediment and stable isotope measurements in three of the thirteen lakes. We demonstrate that AOM is widespread in freshwater lake sediments and accounts for 29%-34% (95% confidence interval) of the mean total CH4 produced in surface and near-surface lake sediments. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: sediment incubations; methanotrophy; methanogenesis; electron acceptors; stable isotopes